Chicken Feed Business Analysis in Palu City - Afandi, Afandi; Syukur, Syukur; Aswad, Aswad (AgriSains, 2019)
The research aims to analyze the income and business feasibility of selling chicken fodder in Palu City. The study was conducted in Palu City, from January-Februari 2019. The study used a model of revenue analysis and business feasibility analysis with R / C (Revenue Cost Ratio) and Break Event Point (BEP) criteria. The results showed that the average business income of selling chicken feed in Palu City was Rp10,133,419,048/year. The feasibility test of the average chicken feed sales business in the city of Palu by using criteria (RC Ratio)> 1, then the business was declared feasible with a value of R / C = 25.5 and the Break Event Point (BEP) resulted in a positive value.